Some productivity indices of heterogeneous rabbits under a pastured system - Oseni, S.O.; Bashiru, H.A. (Nigerian Journal of Animal Science, 2023)
The study evaluated the productivity indices of heterogeneous rabbits under a pastured system. Data on 56 litters across three parities from 5 bucks and 22 does were analyzed. Fertility, reproductive and growth performance traits included number of mating per conception (NMC), litter size at kindling (LSK), litter sizes and weights at 7, 14, 21, 28, and 56-day post-kindling, survival rate (SR) and daily weight gain of kits from kindling to weaning. Data were analyzed using the General Linear Model (GLM) procedure of SAS®. A linear model that included fixed effects of LSK classes (low, medium and high), doe weight at conception (light, medium and heavy does) and parity (1st, 2nd or 3rd) was used. Results showed that superior growth and reproductive performance in terms of LSK and number born alive were obtained in later parities (parities 2 and 3). Kit weight and daily gain at kindling and at 7, 14, 21, 28 and 56 d were significantly higher in low-sized litters when compared with medium- and large-sized litters (P<0.05). It was concluded that genetic improvement programmes for heterogeneous rabbit population should consider traits such as LSK, doe weight at conception, and VNB at kindling, for optimum productivity and that smallholder and commercial rabbit farmers should also consider these traits to maximize profits under low input systems.